6
$\begingroup$

i cannot figure out a way to find this limit. $$\displaystyle\lim_{n\to \infty} n^2(\sqrt[n]{2}-\sqrt[n+1]{2})$$

Its undeterminate form $0\cdot\infty$ so i tried using $$\displaystyle\lim_{n\to \infty}\frac{a^{X_n}-1}{X_n}=\ln{a}$$ this leads to $0\cdot\infty$ again. I then tried to transform it in $\frac{0}{0}$ $$\displaystyle\lim_{n\to \infty} \frac{\sqrt[n]{2}-\sqrt[n+1]{2}}{\frac{1}{n^2}}$$ here i dont know what i could do to find the limit.

$\endgroup$
  • $\begingroup$ Are you allowed to use Hopital's rule? I guess, you are not. $\endgroup$ – mrs Jan 27 '13 at 10:45
  • $\begingroup$ Hint: $e^x=1+x+x^2/2+O(x^3)$ as $x\to0$. $\endgroup$ – Hanul Jeon Jan 27 '13 at 10:45
  • $\begingroup$ I am not allowed to use Hopital's rule and i do not know big O notation. $\endgroup$ – phi Jan 27 '13 at 10:46
10
$\begingroup$

Write

$$2^{\frac{1}{n}} = e^{\frac{\log{2}}{n}}$$

so that

$$\begin{align} \lim_{n \rightarrow \infty} n^2 \left (2^{\frac{1}{n}} - 2^{\frac{1}{n+1}} \right ) &= \lim_{n \rightarrow \infty} n^2 \left (e^{\frac{\log{2}}{n}} - e^{\frac{\log{2}}{n+1}} \right ) \\ &= \lim_{n \rightarrow \infty} n^2 \log{2} \left ( \frac{1}{n} - \frac{1}{n+1}\right ) \\ &= \lim_{n \rightarrow \infty} \frac{n \log{2}}{n+1} \\ &= \log{2} \\ \end{align} $$

The second step relies on the fact that

$$e^x = 1+ x + O(x^2)$$

as $x \rightarrow 0$.

$\endgroup$
  • $\begingroup$ You actually have to be a little more careful here: while it's true that the $O(x^2)$ terms cancel when you expand out $e^x$ for $x=\frac{\log 2}{n}$ and $x=\frac{\log 2}{n+1}$, that's not necessarily self-evident on the face of it, and of course because we're multiplying by $n^2$, if those second-order terms didn't cancel then they'd contribute a finite amount to the solution. Better to expand out to order 3. $\endgroup$ – Steven Stadnicki Jan 28 '13 at 3:24
  • $\begingroup$ @StevenStadnicki: You make a good point, although as you know the $k$th-order term provides a contribution of $O(n^{1-k})$ to the limit piece, which of course goes to zero in this limit when $k>1$. I could have been more explicit about that. $\endgroup$ – Ron Gordon Jan 28 '13 at 10:04
10
$\begingroup$

By the mean value theorem $$\displaystyle\lim_{n\to \infty} n^2(\sqrt[n]{2}-\sqrt[n+1]{2})=\displaystyle\lim_{n\to \infty} \left(n^2 \times\frac{2^{1/c_{n}}\ln 2}{c_n^2}\right)=\ln2$$ where $n<c_n<n+1$

Chris.

$\endgroup$
  • 1
    $\begingroup$ this is an outstanding solution $\endgroup$ – user29743 Jan 28 '13 at 2:33
  • $\begingroup$ @countinghaus To be fair, L'Hôpital is just a clever application of the intermediate value theorem too. $\endgroup$ – Pedro Tamaroff Feb 27 '13 at 2:32
4
$\begingroup$

We have:

$ \begin{align*} \lim_{n\to \infty} n^2(\sqrt[n]{2}-\sqrt[n+1]{2}) & = \lim_{n\to \infty} n^2\left( 2^{\frac{1}{n}} - 2^{\frac{1}{n+1}} \right) = \lim_{n\to \infty} n^2 2^{\frac{1}{n+1}} \left( 2^{\frac{1}{n}-\frac{1}{n+1}} - 1 \right) \\ & = \lim_{n\to \infty} n^2 2^{\frac{1}{n+1}} \left( 2^{\frac{1}{n^2+n}} - 1 \right) \\ & = \lim_{n\to \infty} \cfrac{n^2 2^{\frac{1}{n+1}} \left( 2^{\frac{1}{n^2+n}} - 1 \right)}{\cfrac{1}{n^2+n}(n^2+n)} \\ & = \lim_{n\to \infty} \dfrac{n^2}{n^2+n} \cdot \lim_{n\to \infty} 2^{\frac{1}{n+1}} \cdot \lim_{n\to \infty} \cfrac{2^{\frac{1}{n^2+n}} - 1}{\cfrac{1}{n^2+n}} \\ & = 1 \cdot 1 \cdot \ln 2 \\ & = \boxed{\ln 2}. \end{align*} $

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.